2021
DOI: 10.1007/s12519-020-00406-9
|View full text |Cite
|
Sign up to set email alerts
|

ECIEN-2020 study: the effect of COVID-19 on admissions for non-COVID-19 diseases

Abstract: Background The pandemic caused by severe acute respiratory coronavirus 2 (SARS-CoV-2) has had great effects on health systems worldwide, not only in relation to coronavirus disease 2019 (COVID-19) cases but also affecting patients with other pathologies. Methods ECIEN-2020 is an observational study conducted in a tertiary referral hospital in Navarra, Spain. It describes the effects of COVID-19 pandemic and the preventive measures adopted, in pediatric admissions for non-COVID-19 diseases. Admissions during Ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
3
10
0
Order By: Relevance
“…This was sharply in contrast with a steady increase in referrals for growth issues that we reported from 2014 to 2018 in a previous study [ 1 ], even though the criteria – according to the Italian Medicines Agency (AIFA) – to perform stimulation tests were the same (i.e., height ≤ − 3 SD; or height ≤ − 2 SD + growth velocity per year ≤ − 1 DS for age and sex evaluated for at least 6 months or a reduction of height of 0.5 SD per year in children > 2 years of age; or height ≤ − 1.5 SD compared to target height and growth velocity per year ≤ − 2 SD or ≤ − 1.5 SD for two consecutive years; or growth velocity per year ≤ − 2 SD or ≤ − 1.5 SD after two consecutive years, even without short stature and after exclusion of other causes of failure to thrive; or malformations/lesions of hypothalamus/pituitary demonstrated at brain MRI) [ 13 ]. Although this is the first study reporting a decrease of referrals for suspected GHD during 2020 lockdowns, our results align with previous reports addressing a delay of hospital care admissions and a reduction of 30–40% in visits during the COVID-19 pandemic [ 9 , 10 ]. A possible explanation for the decrease in tests for suspected GHD is that well-child visits were canceled during the pandemics, removing a chance for family pediatricians to detect short stature and delayed growth.…”
Section: Discussionsupporting
confidence: 91%
“…This was sharply in contrast with a steady increase in referrals for growth issues that we reported from 2014 to 2018 in a previous study [ 1 ], even though the criteria – according to the Italian Medicines Agency (AIFA) – to perform stimulation tests were the same (i.e., height ≤ − 3 SD; or height ≤ − 2 SD + growth velocity per year ≤ − 1 DS for age and sex evaluated for at least 6 months or a reduction of height of 0.5 SD per year in children > 2 years of age; or height ≤ − 1.5 SD compared to target height and growth velocity per year ≤ − 2 SD or ≤ − 1.5 SD for two consecutive years; or growth velocity per year ≤ − 2 SD or ≤ − 1.5 SD after two consecutive years, even without short stature and after exclusion of other causes of failure to thrive; or malformations/lesions of hypothalamus/pituitary demonstrated at brain MRI) [ 13 ]. Although this is the first study reporting a decrease of referrals for suspected GHD during 2020 lockdowns, our results align with previous reports addressing a delay of hospital care admissions and a reduction of 30–40% in visits during the COVID-19 pandemic [ 9 , 10 ]. A possible explanation for the decrease in tests for suspected GHD is that well-child visits were canceled during the pandemics, removing a chance for family pediatricians to detect short stature and delayed growth.…”
Section: Discussionsupporting
confidence: 91%
“…Among symptomatic patients, fever (>38 • C) was the most common symptom (37/41), with a mean duration of 3.11 days (SD 3.01). An epidemiological description of all pediatric patients with laboratory confirmed COVID-19 in Navarre, and a more detailed description of the CHN hospitalized patients have been performed [6,7,33]. No mortality, severe pulmonary complications or pulmonary emboli were detected in our study.…”
Section: Resultsmentioning
confidence: 72%
“…A Spanish study reported a reduction in pediatric ED visits during the country’s first pandemic wave, although the percentage of hospitalizations following ED visits had doubled [ 17 ]. This finding is suggestive of a tendency for parents to refrain from presenting their children at the ED during the pandemic, in absence of severe health conditions [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%